Do Muslim women need saving? - Abu-Lughod, Lila. (Cambridge, Massachusetts : Harvard University Press, 2013)
"Frequent reports of honor killings, disfigurement, and sensational abuse have given rise to a consensus in the West, a message propagated by human rights groups and the media: Muslim women need to be rescued. Lila Abu-Lughod boldly challenges this conclusion. An anthropologist who has been writing about Arab women for thirty years, she delves into the predicaments of Muslim women today, questioning whether generalizations about Islamic culture can explain the hardships these women face and asking what motivates particular individuals and institutions to promote their rights." -- Publisher website.
Introduction : rights and lives -- Do Muslim women (still) need saving? -- The new common sense -- Authorizing moral crusades -- Seductions of the "honor crime" -- The social life of Muslim women's rights -- An anthropologist in the territory of rights -- Conclusion : registers of humanity.
Includes bibliographical references and index.
Keywords: Muslim women -- Social conditions; Muslim women -- Civil rights; Women's rights -- Islamic countries